Driving a greater understanding of non-communicable diseases in Africa through collaborative research: the experience of the GSK Africa NCD Open Lab - Sally Gatsi; Mike Strange; Ann Dufton; Pauline Williams; Juliet Addo (Inishmore Laser Scientific Publishing Ltd, 2018)
# Background The majority of premature deaths from non-communicable diseases (NCDs) occur in low-income countries. However, clinical research in these patient populations is generally lacking. Thus, many treatment paradigms for NCDs are either absent or extrapolated from populations with different genetics, health needs, and socio-economic circumstances. # Methods To evaluate the outcomes from the first call for proposals from the GSK Africa NCD Open Lab. Funding was offered to research projects aiming to improve understanding and generate new knowledge of NCDs in African populations. Proposals were sought for projects relating to cancer, cardiovascular disease, diabetes, chronic respiratory disease or chronic kidney diseases. The proposal had to be led by African scientists from Cameroon, The Gambia, Ghana, Kenya, Côte d'Ivoire, Malawi, Nigeria or Uganda and include a capacity building component. # Results The 155 eligible proposals covered oncology (31.0%), cardiovascular disease (27.1%), metabolic disorders such as diabetes (20.6%), chronic respiratory disease (9.7%) and chronic kidney disease (6.5%). Most applications were from Nigeria (37.8%), Kenya (17.3%) and Uganda (13.5%). Following initial review, 23 proposals were considered by a Scientific Advisory Board, and ten were invited to submit full applications. Five projects were funded in cardiovascular disease, the interaction between cardiovascular disease and HIV infection, breast cancer, asthma and chronic kidney disease/diabetes. Principal investigators were from Nigeria, Uganda and Malawi with collaborators from Cameroon, Ethiopia, Kenya, Mozambique, South Africa, the UK, USA and the Netherlands. All of the projects involved research capacity strengthening elements. # Conclusions These projects have the potential to improve the understanding of the aetiology and natural history of specific NCDs, while also informing the development of clinical guidelines for the effective management of disease. However, far more needs to be done to address capacity building and funding for NCD research in Africa.